Elastic Stable Intramedullary Nailing (ESIN) of Pediatric Metacarpal Fractures: Experiences with 66 Cases - Lieber, Justus; Härter, Bettina; Schmid, Eckhard; Kirschner, Hans Joachim; Schmittenbecher, Peter P (European Journal of Pediatric Surgery, 2012)
Introduction Elastic stable intramedullary nailing (ESIN) is the first-choice surgical technique for stabilizing various pediatric diaphyseal and selected metaphyseal fractures of the long bones. This technique has increasingly been applied in fractures of the small bones. Here, we report experiences with ESIN in displaced fractures of the metacarpals in children.Patients and Methods Retrospective data analysis of metacarpal fractures in children stabilized by ESIN in three pediatric trauma centers between 2003 and 2009. Indication for intervention was total displacement or axial deviation >10 degrees in the frontal plane and/or >30 degrees in the sagittal view.Results A total of 66 cases of metacarpal fractures (51 right hand and 12 left hand) treated by ESIN were found in 63 children (mean age 13.3 years; range 4.0 to 16.1) over the study period. Of these, 55 fractures affected metacarpal 5, 6 fractures affected metacarpal 4, 3 fractures affected metacarpal 1, and 2 fractures occurred at metacarpal 2. Mean operating time was 21 minutes (range 5 to 54), titanium elastic nails were used with a diameter of 1.5 mm (n = 23), 2.0 mm (n = 42), and 2.5 mm (n = 1). Single ESIN implantation was performed in 63 cases; in 3 cases, two nails were implanted. Eleven patients received additional immobilization due to nondisplaced additional fractures of the phalanx (n = 2) or for analgetic treatment (n = 9). Five complications were registered (7.6%). In two cases recurrent fracture dislocation occurred, one of them requiring revision of the osteosynthesis. In other two cases irritation of the extensor tendons occurred, one of them requiring secondary tendon plasty. One persisting cutaneous hyposensibility after ESIN of a metacarpal 5 fracture was reported. All fractures healed uneventfully and metal removal was performed after a mean of 92 days (range 31 to 104). After a mean follow-up of 26 months (range 2 to 74), all patients had full range of movement and cosmetic results were described as good and satisfactory by all patients.Conclusion ESIN of the metacarpals is a safe, minimally invasive, and technically easy option in displaced fractures that warrant surgical intervention achieving excellent long-term results. Complications occurred when technical aspects to obtain stability were neglected or tendons and nerves of the hand had been injured. Stabilizing fractures of metacarpal 1 is technically challenging when compared with fractures of metacarpals 2 to 5.
Keywords: pediatric trauma; metacarpal fracture; elastic stable intramedullary nailing; complication